Jejum pré-anestésico em gatos adultos jovens (Felis silvestris catus) - Castro, Jorge Luiz Costa (2014)
The study was divided into four papers. The first, aimed to conduct a literature review of preoperative fasting in dogs and cats emphasizing the time recommended in the literature and its peculiarities. The second objective was to evaluate the appropriate period of fasting for elective anesthesia and surgical procedures in cats, by analysis of gastric emptying time based on the daily energy requirement by comparing the fasting time of 4 or 8hours with dry or wet food. The research involved four phases of evaluation at intervals of 7 days, with seven female cats in fasting and anesthetized for 30 minutes and evaluated by gastroscopy. All animals were submitted to gastric biopsy for histologic evaluation, search of Helicobacter ssp, and ruling out morphological alterations. All cats were anesthetized mimetizing the surgical time of an elective surgery. The evaluation was performed with a 9.7 mm flexible gastrointestinal endoscope. Apart from clinical inspection biochemical tests were performed in order to determine glucose, lactate, cholesterol and albumin levels in samples previously collected after the fasting. The animals were monitored clinically until three months after the latter group to be completed. The fasting time of 4 and 8 hours with paste food promoted full gastric emptying and five cats showed no complete gastric emptying in 8 hours of fasting with dry food. The third study aimed to evaluate the esophageal and gastric pH using dry feeding and fasting period of eight hours. Seven cats were fed with dry food and went through 8 hours of preoperative fasting. Esophageal and gastric pH were evaluated after anesthetic induction, and esophageal pH during recovery from anesthesia until six hours after anesthetic induction. An esophageal pH meter Scophe Dynamed® was used, to evaluate the cats. The device was connected to a transnasal catheter of which the tip was positioned 2 cm from the lower esophageal sphincter, and the pH was continuously monitored and recorded every 5 minutes for a period of 360 minutes. The average pH was 6.49 ± 0.42 in the esophagus and 1.50 ± 0.31 in the stomach. There was no statistical difference between esophageal and gastric pH in anesthetic induction with the protocol used. There was also no gastroesophageal reflux (GER) during the next six hours. The fourth article aimed to compare pH monitoring in two different types of preoperative fasting, 8 hours with dry food (12 % moisture) and 4 hours with pasty food (80 % moisture). Seven cats were divided into two groups A (dry diet and time of 8 hours of preoperative fasting) and B (paste diet and time of 4 hours of pre -operative fasting) were used. In group A and B pH monitoring was performed, and a followed up was made for six hours from the time of anesthetic induction T0 to 360 minutes (T13). The average pH in the esophagus in group A was statistically higher than group B. The average pH in the stomach of group A was statistically lower than group B. The average pH in the esophagus of group A was statistically superior to the stomach. The average pH in the esophagus of group B was statistically superior to the stomach. In addition when comparing the recovery times the average pH of the A group did not significantly vary between the times (P<0.05) while the average pH of Group B varied significantly between times 4 and 5; 11 and 12. As conclusions of this study it was found that 4 hours with moist feed allows complete emptying of the stomach and fasting 8 hours with dry feed may have gastric contents while no change in gastric and esophageal pH in both fasting times without risk of gastroesophageal reflux.